Analisis Perbandingan Sistem Harta Warisan Perkawinan Dalam Kuhperdata dan Hukum Adat: Studi Kasus Masyarakat Multikultural - Manik, Alvin Putra Hariando; Siahaan, Parlaungan Gabriel; Gea, Benediktus Josua; Aqilah, Zahra Nur; Zega, Sarah Theresia; Damanik, Agnes Elsonya; Manurung, Thessa D Triputri (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the comparison of the marital property system in the Civil Code and customary law in a multicultural society. This study uses a qualitative research method with observation, interview and documentation studies. The results of the study indicate that there are significant differences between the marital property system in the Civil Code and customary law, especially in terms of the distribution of inheritance. The Civil Code regulates marital property as joint property owned by husband and wife, while customary law has various variations in regulating marital property. This study also shows that multicultural societies have different cultural and customary law diversity, thus creating challenges in implementing a fair marital property system that is in accordance with the needs of the community.